Relationship Between Organizational Culture To Lecturer Performance Professionalism In Islamic Religion Faculty University Of Muhammadiyah Sumatera Utara - Juli Maini Sitepu; Robie Fanreza (Proceeding International Seminar of Islamic Studies, 2019)
This study aims to find the relationship between organizational culture and professionalism of lecturers' performance at the Faculty of Islamic Religion. Regarding the research to be used is quantitative research with data collection methods that use the scale of organizational culture and the scale of professionalism of performance improvement for each variable (X and Y). The samples in this study were 31 permanent lecturers at the Faculty of Islam. The data obtained were analyzed using the SPSS version 22 application. Obtained the results obtained were analyzed then obtained F = 9, 726 and p = 0.02 (p <0.05), which means significant so that the hypothesis is accepted. This shows that organizational culture is related to the professionalism of the performance of lecturers at FAI UMSU